Self-Esteem Orientation in History Learning - Jamil, Robit Nurul (Budapest International Research and Critics University, 2021)
Historical education in the context of learning must offer value solutions in overcoming character problems. This urgency should be understood by all history educators as the mandate of history is a heritage of values, it is necessary to absorb values, so that the goal of history to make people wise will be achieved. Self-esteem is one aspect of personality that has an important role and has a major influence on individual attitudes and behavior. This value is very important to support the national identity and character of students. The dynamics of modernization requires a container of values in cultural transformation, so that students who are citizens have filters to sort out the impact of the current modernization. The method used in this scientific paper is a qualitative paradigm (qualitative description). The results of the discussion 1. Explanation of self-esteem in character building 2. The position of history learning in growing self-esteem. Conclusions 1. Self-esteem has a major influence in the formation of students' character 2. History learning is a bridge for students' character growth. 3. Character building is very difficult in national education if learning is not oriented towards certain values.